Pengaruh Likuiditas Dan Struktur Modal Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderating Pada Perusahaan Sektor Consumer Non-Cyclicals Yang Terdaftar Di Bei Tahun 2020-2024 - Ayu Anggraini; Berta Agus Petra; Nila Pratiwi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to determine the relationship between the influence of liquidity and capital structure on firm value with dividend policy as a moderating variable. The population used in this study were 131 Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024 obtained from www.idx.co.id. The sampling technique used was purposive sampling and obtained 27 Consumer Non-Cyclicals sector companies as samples. The data analysis methods used in this study were descriptive statistical tests, classical assumption tests, panel data regression analysis and hypothesis testing using eviews 12. The results of the study indicate that a) liquidity partially has no significant effect on firm value b) capital structure partially has a significant positive effect on firm value c) dividend policy is unable to moderate the positive and significant effect of liquidity on firm value d) dividend policy is able to moderate the positive and significant effect of capital structure on firm value.